RGO/MgO hybrid nanocomposites with high specific capacitance. Issue 1 (January 2018) - Das, Pradip Sekhar; Bakuli, Suvajit; Biswas, Indranil; Mallik, Awadesh Kumar; Dey, Arjun; Mukherjee, Smita; Ghosh, Jiten; Mukhopadhyay, Anoop Kumar
Abstract: A scalable, cost effective synthesis of reduced graphene oxide (RGO)-magnesium oxide (MgO) hybrid nanocomposite (RGOMOHNC) is reported in the present work. The process involves an in-situ sonication method in aqueous medium at room temperature e.g., 30 °C. The as synthesized graphene oxide (GO) and RGOMOHNC powders are characterized by the XRD, FESEM, TEM, FTIR, RS and XPS techniques. The results indicate that in-situ growth of 20–30 nm MgO nanoparticles effectively increases the graphitic nature of the layered RGO microstructure. The experimentally measured cyclic voltammetry (CV) plots show that the specific capacitance of the RGOMOHNC powders is three orders of magnitude higher than that of the GO powders. A mechanism of RGOMOHNC formation has been proposed.